Tanggung jawab finansial generasi sandwich dalam perspektif ketahanan keluarga - Najiya, Usluki (Maliki Interdisciplinary Journal, 2025)
During their productive period, a person with the sandwich generation has a dual role in meeting their needs, namely elderly parents and their children. This dual financial responsibility will have an impact on family resilience in terms of economy, social, and psychology. This study uses a qualitative approach based on literature review. With the support of family resilience theory, this study attempts to examine how the sandwich generation maintains the function and welfare of their family with a dual financial burden. The discussion explains that the financial conditions experienced by the sandwich generation have a very negative impact on the harmony and balance of family roles. On the other hand, this condition also brings adaptive strategies such as the quality of financial management. With the current socio-economic dynamics, this study explains the importance of state and community support for someone with dual financial responsibilities (the sandwich generation)